2018
DOI: 10.1177/1833358317749162
|View full text |Cite
|
Sign up to set email alerts
|

Secondary use of hospital information system data for safe bedside radiography in terms of patient factors

Abstract: Our results suggested that the secondary use of HIS data for the quantitative evaluation of patient factors and implementation of those quantitative values in medical records may be useful for the safe performance of bedside radiography as well as providing a method of decision support for doctors to order bedside radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These included a shortage of registers; incompetence in staff members’ handling of data; omission of some indicators in DHIS2 and frequent changes in some indicators and forms in DHIS2. The literature has suggested that these challenges are not new in Africa (Ojo, 2018; Sasaki et al, 2018; Smith et al, 2007) and may be linked to the fact that development of HIS in Africa has encountered serious problems due to substantial disparities in access to resources, including human resources. These resource insufficiencies in the health sector, coupled with the burden of disease, poor indicators and frail and unsuitable health systems are exacerbated by extreme poverty (Ssekitooleko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These included a shortage of registers; incompetence in staff members’ handling of data; omission of some indicators in DHIS2 and frequent changes in some indicators and forms in DHIS2. The literature has suggested that these challenges are not new in Africa (Ojo, 2018; Sasaki et al, 2018; Smith et al, 2007) and may be linked to the fact that development of HIS in Africa has encountered serious problems due to substantial disparities in access to resources, including human resources. These resource insufficiencies in the health sector, coupled with the burden of disease, poor indicators and frail and unsuitable health systems are exacerbated by extreme poverty (Ssekitooleko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among medical professionals, nurses have the closest daily contact with patients, and are most likely to notice and record changes in the conditions of patient. Nurses carefully monitor patients, maintain records on their current conditions, and predict possible future changes in their conditions (Imai & Takase, 2017; Sasaki et al, 2019). Their records are a valuable source of information to other medical staff.…”
Section: Nursing Observation Recordsmentioning
confidence: 99%